(untitled) (Scientific journal of the Fergana State University, 2024)
The educational process in higher education sets itself the task of training highly qualified specialists with deep knowledge, professional skills and abilities and able to apply them in practice. But in our time, the ability to use the accumulated experience of society, the ability to create, and solve problems should be more important. Future specialists in physical culture and sports should not be indifferent to the problems of our society, they should have high professional and moral qualities. In addition, it should be noted that the professional and creative development of the personality of a future specialist becomes the main goal of higher education. All this fully applies to the training of specialists in physical culture and sports. Today, there is an acute public demand not only for the general intellectual and professional creative activity of the individual, but also for new, new thinking. Therefore, the main focus of training should be personal development.